POTRAIT OF ENGLISH TEACHING IN ELEMENTARY SCHOOL OF SD PATRA MANDIRI 2 PALEMBANG VIEWED FROM KURIKULUM MERDEKA - Sulthan Ghazi Al Ghifari; Djunaidi; Marleni (Esteem Journal of English Education Study Programme, 2025)
This research investigates the implementation of the Kurikulum Merdeka in the context of English language instruction at SD Patra Mandiri 2 Palembang, with particular attention to its learner-centered orientation and the pedagogical challenges encountered by educators. Employing a qualitative descriptive approach, data were gathered through classroom observations, an in-depth interview with an English teacher, and questionnaires administered to 22 fifth-grade students. The findings indicate that the curriculum is enacted through dynamic and participatory strategies such as educational games, collaborative group discussions, and project-based learning exemplified by activities like the "My Dream House" poster project which foster greater student engagement and promote the integration of multiple language competencies. Despite these pedagogical strengths, teachers face significant hurdles, including inadequate access to technological resources (e.g., multimedia projectors and reliable internet), difficulties in fostering student autonomy, and the labor-intensive nature of evaluating project-based work. While students generally demonstrate enthusiasm and engagement, they also struggle with vocabulary acquisition and oral communication confidence. The study underscores the pressing need for enhanced infrastructural support, sustained professional development for educators, and differentiated instructional strategies to meet the heterogeneous needs of learners.